Nutidige dramatikeres skriveproces - Moosmann, Daniela; Ejgod Hansen, Louise (Peripeti, 2021)
Daniela Moorman develops a conceptual tool for understanding the process of writing a play. She draws on the work of several contemporary playwrights, including Arne Sierens, Gerardjan Rijnders and René Pollesch.